Uwarunkowania poczucia szczęścia małżeńskiego w opinii kobiet i mężczyzn - Wosik-Kawala, Danuta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The aim of the undertaken research was to diagnose the conditions of the sense of marital happiness in the perception of women and men. The research was conducted among women and men aged from 19 to 65 years. As a research method, a diagnostic survey using a questionnaire as a research technique was used. The obtained research results may contribute to an increase in the awareness of women and men about the conditions necessary for the sense of marital happiness, and consequently have an impact on the sense of marital satisfaction, as well as counteract many marital conflicts. The obtained research results may contribute to an increase in the awareness of women and men about the conditions necessary for the sense of marital happiness, and consequently have an impact on the sense of marital satisfaction, as well as counteract many marital conflicts.
Keywords: family; marriage; happiness; marital happiness